The Spirit of the Place and the Place of the Spirit: Local Spirits, Boundaries, and Social Order in Southwest Finnish Folklore - Björkman, John (Temenos, 2021)
Southwest Finnish folklore recorded in the early twentieth century contains a wealth of legends about local spirits, residing and acting both in the wilderness and on farm premises. They belong to belief systems that express social norms and regulations. Many of the legends contain enough information to allow us to locate exactly where local spirits are said to appear or interact with people. In this paper I study these locations and their place in the structure of village society, using historical village maps. The results shed new light on the nature of borders and boundaries in folklore and vernacular belief, as well as on the view of the social meaning of local spirits. Borders and border zones are common ground between several societies, lacking a clearly defined master. In places of uncertain mastery local spirits, endowed with taboos and the authority of the surrounding societies, play a social role in regulating the activities of people on such common ground.